Why is socially‐just climate change adaptation in sub‐Saharan Africa so challenging? A review of barriers identified from empirical cases. (4th February 2015) - Shackleton, Sheona; Ziervogel, Gina; Sallu, Susannah; Gill, Thomas; Tschakert, Petra
<x xml:space="preserve">Abstract</x> To enhance understanding of the process of climate change adaptation and to facilitate the planning and implementation of socially‐just adaptation strategies, deeper consideration of the factors that impede adaptation is required. In response, scholars have increasingly identified barriers to adaptation in the literature. But, despite this progress, knowledge of barriers that hamper adaptation in developing countries remains limited, especially in relation to underlying causes of vulnerability and low adaptive capacity. To further improve understanding of barriers to adaptation and identify gaps in the state‐of‐the‐art knowledge, we undertook a synthesis of empirical literature from sub‐Saharan Africa focusing on vulnerable, natural resource‐dependent communities and livelihoods. Our review illustrates that: (1) local‐level studies that reveal barriers to adaptation are diverse, although there is a propensity for studies on small‐holder farmers; (2) many of the studies identify several barriers to adaptation, but appreciation of their interactions and compounded impacts remains scarce; and (3) most of the barriers uncovered relate broadly to biophysical, knowledge, and financial constraints on agricultural production and rural development. More hidden and under‐acknowledged political, social, and psychological barriers are rarely mentioned, unless captured in studies that specifically set out to investigate these. We finish our review by highlighting gaps in understanding and by suggesting future research directions, focusing on issues of social justice. We argue that research on barriers needs to start asking why these barriers emerge, how they work together to shape adaptation processes, who they affect most, and what is needed to overcome them. WIREs Clim Change 2015, 6:321–344. doi: 10.1002/wcc.335 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.